Pertumbuhan Kacang Tanah Di Media Tanam Yang Berbeda (Tanah, Kompos, Dan Pasir) - Lilis Sartika Gulo; Enjelita Telaumbanua; Gustin Fanolo Bate'e; Perti Citra Damarni Waruwu; Newyear Risman Jaya Harefa; Yoel Melsaro Larosa (CV. SINAR HOWUHOWU, 2025)
This study aims to evaluate the effects of different growing media—soil, compost, and sand—on the growth of peanut (Arachis hypogaea L.) plants. The experiment was conducted using a Completely Randomized Design (CRD) with three treatments and five replications. Growth parameters including plant height, number of leaves, and root length were observed over an eight-week period. The results indicated that the type of growing medium had a significant effect on all measured parameters. Plants grown in compost exhibited the highest average plant height and number of leaves, followed by those grown in soil. In contrast, sand produced the lowest growth performance. Although the longest root length was observed in plants grown in sand, this was likely a response to water and nutrient stress. Compost proved to be the most effective medium for supporting healthy and uniform peanut growth. These findings suggest that compost, as an organic-rich growing medium, can significantly improve peanut cultivation and serve as a sustainable option for areas with limited fertile soil.